Antimicrobial peptides of fish: innocuous alternatives to antibiotics. (2nd November 2018) - Chaturvedi, Preeti; Bhat, Raja Aadil Hussain; Pande, Amit
Abstract: Antimicrobial peptides (AMPs) are the key components of the innate immune system and perform the various biological function which offers immunocompetence and homeostasis to the living organisms. Owing to their multidimensional properties, they can find an important role in therapeutics for the treatment of emerging diseases in fishes. Several AMPs are reported in fishes, including defensins, cathelicidins, hepcidins, histone‐derived peptides and piscidins having board antimicrobial spectrum. Various factors are necessary for the induction of AMPs expression like pathogen‐associated molecular patterns and damage‐associated molecular pattern. Moreover, with beneficial effects, AMPs are coupled with rare concerns which should be considered before bringing them under the label of 'harmless alternative to antibiotics'.